The CT scanner as a therapy machine - Iwamoto, K.S.; Norman, A.; Kagan, A.R.; Wollin, M.; Olch, A.; Bellotti, J.; Ingram, M.; Skillen, R.G. (Radiotherapy and oncology, 1990)
Many tumors in the brain and in other tissues can be delineated precisely in images obtained with a CT scanner. After the scan is obtained the patient is taken to another room for radiation therapy and is positioned in the beam with the aid of eternal markers, simulators or stereotactic devices. This procedure is time consuming and subject to error when precise localization of the beam is desired. The CT scanner itself, with the addition of a collimator, is capable of delivering radiation therapy with great precision without the need for external markers. The patient can be scanned and treated on the same table, the isocenter of the beam can be placed precisely in the center of the lesion, the beam can be restricted to just those planes in which the lesion appears, several arcs can be obtained by simply tilting the gantry, and the position of the patient in the beam can be monitored continuously during therapy. We describe here the properties of the CTX, the CT scanner modified for therapy.